The Diagnostic and Prognostic Roles of Combined Expression of Novel Biomarkers in Lung Adenocarcinoma (LUAD) and Lung Squamous Cell Carcinoma (LUSC); An Immunohistochemical Study - Mohamed Alabiad; Ola Harb; Mohamed Abozaid; Ahmed Embaby; Doaa Mandour; Rehab Hemeda; Amany Shalaby (Iranian Society of Pathology, 2020)
Background and Objective: Diagnosis and discrimination of lung adenocarcinoma (LUAD) from lung squamous cell carcinoma (LUSC) is critical to select the appropriate treatment regimen as recently targeted therapies require accurate subtyping of NSCLCs. There are currently several biomarkers that could be used for differentiation between LUAD and LUSC, but they have less sensitivity, specificity, and clinical applicability. The aimof this study was to assess the diagnostic and prognostic values of CLCA2, SPATS2, ST6GALNAC1, and Adipophilin tissue expression in the tissues retrieved from LUAD and LUSC patients using immunohistochemistry. Methods:The current study was performed on the samples retrieved from sixty primary lung masses that were diagnosed as LUAD and LUSC. Immunohistochemistry was performed by using a panel of CLCA2, SPATS2, and ST6GALNAC1. We assessed the diagnostic roles of the studied markers in the discrimination between LUAD and LUSC and their prognostic values. Results: SPATS2 and CLCA2were expressed more in LUSC than LUAD. ST6GALNAC1 and Adipophilin were expressed more in LUAD than LUSC (p <0.001). The sensitivity and specificity of CLCA2, SPATS2, ST6GALNAC1 and Adipophilin in adequate subtyping and reaching the accurate diagnosis was 100%. We found only significant differences in survival rates between the patients with negative and positive CLCA2expression (p =0.038 and p =0.019, respectively). Conclusions: The combination of CLCA2, SPATS2, ST6GALNAC1, and Adipophilin lead to the adequate subtyping of lung cancer and reaching accurate diagnosis with the highest sensitivity and specificity.